2014
DOI: 10.22164/isea.v8i1.89
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Awareness and The Role of Public Accounting Professional Bodies in Indonesia: A Brief Reflection

Abstract: This study aims to give an insight about environmental awareness from public accountant and the role of Indonesian accounting professional bodies in ensuring professional sustainability. A naturalistic method was  applied to get deep understanding about the perspectives of the boards of professional bodies as a representation from the condition of public accountants in general. Data collection methods used in this study were interviews and focus group discussion. The findings highlight a variety of perspective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…This is due to the fact that it supports stock market development and openness; honors the public trust, and sustains innovation in the digital era. Thus, the regeneration process becomes crucial (Alimbudiono & Suhartini, 2014;Law & Yuen, 2012;Suryani et al, 2018;Yuliansyah & Suryani, 2016). Data from the Ministry of Finance show that there are only roughly 455 public accounting firms (PPPK-Kemenkeu, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is due to the fact that it supports stock market development and openness; honors the public trust, and sustains innovation in the digital era. Thus, the regeneration process becomes crucial (Alimbudiono & Suhartini, 2014;Law & Yuen, 2012;Suryani et al, 2018;Yuliansyah & Suryani, 2016). Data from the Ministry of Finance show that there are only roughly 455 public accounting firms (PPPK-Kemenkeu, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the ones who select public accounting profession is quite small (Yuliansyah & Suryani, 2016).Previous studies indicated that intention in being a public accountant is influenced by the common perception of the accounting profession as boring and tedious (Sugahara et al, 2008), high workload (Omar et al, 2015), low financial reward (Wen et al, 2018), low job satisfaction, and high employee turnover (Suryani et al, 2018).This results in concerns with regard to the accounting profession in the future, especially in the digital era. Professional sustainability is a hot topic discussed by accountants (Alimbudiono & Suhartini, 2014).…”
Section: Introductionmentioning
confidence: 99%